Surviving in a changing ocean. Tolerance to acidification might affect the susceptibility of polychaetes to chemical contamination. (August 2022) - Munari, Marco; Chiarore, Antonia; Signorini, Silvia Giorgia; Cannavacciuolo, Antonio; Nannini, Matteo; Magni, Stefano; Binelli, Andrea; Gambi, Maria Cristina; Della Torre, Camilla
Abstract: This study aimed to assess the combined effects of ocean acidification (OA) and pollution to the polychaete Syllis prolifera inhabiting the CO2 vent system of the Castello Aragonese (Ischia Island, Italy). We investigated the basal activities of antioxidant enzymes in organisms from the acidified site and from an ambient-pH control site in two different periods of the year. Results showed a limited influence of acidified conditions on the functionality of the antioxidant system. We then investigated the responsiveness of individuals living inside the CO2 vent compared to those from the control to face exposure to acetone and copper. Results highlighted a higher susceptibility of organisms from the vent to acetone and a different response of antioxidant enzymes in individuals from the two sites. Conversely, a higher tolerance to copper was observed in polychaetes from the acidified-site with respect to controls, but any significant oxidative stress was induced at sublethal concentrations. Graphical abstract: Unlabelled Image Highlights: CO2 vent systems are natural laboratory for studying the effects of multiple stressors. We assess the effects of OA and pollution, using polychaetes naturally exposed to OA. Limited influence of OA on the activity of antioxidant enzymes in polychaetes. Polychaetes from the vent were more susceptible to acetone but more tolerant to Cu respect to controls. Tolerance to OA could influence polychaete susceptibility to environmental pollution.